The Effectiveness of Bay Leaf Water Boil Therapy in Reducing Hypertension in Pregnant Women in Ciseureuh Assisted Village, Purwakarta Regency - Ewith Widya Mareta (CV. Inara, 2026)
World Health Organization (WHO) of 70% of known hypertension sufferers only 25% received treatment and only 12.5% ​​were treated well (adequately treated cases) estimated that by 2025 the rate of high blood pressure will increase by 60% and will affect 1.56 billion people worldwide. The purpose of this study was to determine the Effectiveness of Bay Leaf Boiled Water (Syzygium Polyanthum) on Reducing Blood Pressure in Pregnant Women with Hypertension in the Taram Health Center Working Area, Limapuluh Kota Regency in 2020, This type of research is a Quasy Experiment with a One Group Pre test-post test design, purposive sampling technique with a sample of 30 people. Data collection uses observation, then the data is analyzed with a dependent T test. The results of the study showed that the average blood pressure of hypertension sufferers in pregnant women before the intervention was 140.91 mmHg, the average blood pressure of hypertension sufferers in pregnant women after the intervention was 119.09 mmHg, There is the effectiveness of boiled bay leaf water (Syzygium Polyanthum) on reducing blood pressure in pregnant women with hypertension in the assisted village of Ciseureuh in 2026 with (p value = 0.046 <0.05), So it is hoped that the village head can coordinate with other health workers or midwives to be able to increase counseling evenly and comprehensively about mothers with hypertension by using leaflets, brochures and pamphlets about hypertension so that it makes it easier for pregnant women with hypertension to understand it.